2020
DOI: 10.12659/aot.918936
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Does Not Correlate with Behavior toward Deceased Organ Donation: A Cross-Sectional Study in Japan

Abstract: This study was supported by the internal budget of the Saku Central Hospital Group Background: Although knowledge is an important factor that influences decisions regarding deceased organ donation, the associations of knowledge with attitude and behavior regarding organ donation remain uncertain in countries with low organ donation rates like Japan. Material/Methods: We conducted a cross-sectional survey of hospital medical and non-medical staff in 15 Japanese medical facilities. The questionnaire included ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…In an online survey of 1945 Intensive Care Unit (ICU) nurses, health science students and non-health science students in Austria, Stadlbauer V et al showed that the study participants knowledge of Austrian organ donation legislation was high [ 8 ]. In a cross-sectional study survey of 1275 hospital medical and non-medical staff in 15 Japanese medical facilities, Murakami M et al found high knowledge about organ donation and transplantation was associated with willingness to become an organ donor [ 9 ]. Further, in a survey of 724 physicians of different specialties in the USA, Alkhatib AA et al showed physicians who were identified as donors were more aware about issues related to organ shortage [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In an online survey of 1945 Intensive Care Unit (ICU) nurses, health science students and non-health science students in Austria, Stadlbauer V et al showed that the study participants knowledge of Austrian organ donation legislation was high [ 8 ]. In a cross-sectional study survey of 1275 hospital medical and non-medical staff in 15 Japanese medical facilities, Murakami M et al found high knowledge about organ donation and transplantation was associated with willingness to become an organ donor [ 9 ]. Further, in a survey of 724 physicians of different specialties in the USA, Alkhatib AA et al showed physicians who were identified as donors were more aware about issues related to organ shortage [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This retrospective cohort study was conducted at Saku Central Hospital, one of the largest hospitals in eastern Nagano Prefecture, Japan. [ 31 ] Although no full-time transplant surgeons and infectious disease physicians have ever worked in this facility, [ 32 ] it is the only hospital in the area where patients with ESKD can receive living-donor kidney transplantation. [ 33 ] There are 46 beds and 5 full-time nephrologists in the dialysis unit.…”
Section: Methodsmentioning
confidence: 99%
“…Akabayashi [ 18 ] argued that Confucianism, particularly through the principle of filial piety, posed a barrier to organ donation. A survey among medical staff revealed that knowledge about organ donation was not correlated with becoming a registered organ donor, but rather with the willingness to become one [ 19 ]. A long-term survey among medical students highlighted an incomplete understanding of the organ transplantation law and the primary reason cited for becoming an organ donor was “to help others” [ 20 ].…”
Section: Introductionmentioning
confidence: 99%